Examining effects of special heat transfer fins designed for the melting process of PCM and Nano-PCM - Kok, Besir (Pergamon-Elsevier Science Ltd, 2020)
In this study, a new heat transfer fins design, which may improve melting in thermal energy storage, is proposed. First, the melting process in the thermal energy storage without fins is discussed. Then, heat transfer fins are designed to allow the melting of the non-melting regions in TES. These fins are compared with the most widely used fin types in the literature. Melting processes of Base and Nano PCMs with different heat transfer fins are also investigated. The results showed that the development of heat transfer fins has a positive contribution to enhance melting in thermal energy storage systems such as reducing the weight of TES and reducing costs of TES. It is observed that adding fin 2 reduces notably the melting time, but in terms of geometry, fin 1 is more effective in the melting process. In addition, it is found that when inserting fin 1, the PCM melts faster. The melting time has decreased by 63% with the placement of the designed fin in the heat storage tank. However, in the case without fin1, the Nano-PCM is partially melted. The melting ratio at t = 120 min is 98% and 36% for PCM and Nano-PCM, respectively.
Keywords: PCM; Nano-PCM; Heat transfer fins; Thermal energy storage (TES)